2021
DOI: 10.31083/j.rcm2203090
|View full text |Cite
|
Sign up to set email alerts
|

Accurate and early detection of sleepiness, fatigue and stress levels in drivers through Heart Rate Variability parameters: a systematic review

Abstract: Sleepiness, fatigue, and stress in drivers are the leading causes of car crashes. In the late two decades, there is an endeavor to monitor vital signs, stress levels, and fatigue using adapted sensors supported by technological advances. To the best of our knowledge, this systematic review is the first to investigate the role of HRV measurement for sleepiness, fatigue, and stress level monitoring in car drivers. A search was performed in PubMed, Embase, and Cochrane databases using prespecified keywords. Studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Participants with high initial sympathetic nervous activity values showed a decrease in values upon visual stimulation with fresh roses, whereas participants with low initial values showed an increase in values upon visual stimulation. In previous studies, LF/HF of HRV has been reported to increase in awakening and stress states ( Järvelin-Pasanen et al, 2018 ; Thielmann et al, 2021 ) and decrease in drowsy states ( Alexandru et al, 2021 ). So far, nature therapy research has focused on the high LF/HF in the stress state that is decreased by nature-derived stimuli.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Participants with high initial sympathetic nervous activity values showed a decrease in values upon visual stimulation with fresh roses, whereas participants with low initial values showed an increase in values upon visual stimulation. In previous studies, LF/HF of HRV has been reported to increase in awakening and stress states ( Järvelin-Pasanen et al, 2018 ; Thielmann et al, 2021 ) and decrease in drowsy states ( Alexandru et al, 2021 ). So far, nature therapy research has focused on the high LF/HF in the stress state that is decreased by nature-derived stimuli.…”
Section: Resultsmentioning
confidence: 89%
“…The obtained a–a interval time series data were analyzed by the maximum entropy method and high frequency (HF, 0.15–0.40 Hz) and low frequency (LF, 0.04–0.15 Hz) power values were calculated ( Kanaya et al, 2003 ). The LF/HF ratio reflects sympathetic nervous activity ( Pagani et al, 1986 ; Camm et al, 1996 ), which increases during arousal and stress states ( Järvelin-Pasanen et al, 2018 ; Thielmann et al, 2021 ) and decreases during drowsy states ( Alexandru et al, 2021 ). LF/HF data were converted to natural logarithms for normalization ( Kobayashi et al, 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…Changes in cardiac activity, such as HRV (the variation in time between each heartbeat), have been closely linked with the subjective experience of specific psychophysiological states, such as stress, fatigue, sleepiness, and drowsiness (for reviews, see Burlacu et al, 2021; Lu et al, 2022). The beat-to-beat variations in heart rate are mainly produced and intensified through the interplay of the heart and brain, which occurs via the transmission of neural signals through the afferent and efferent pathways of the sympathetic and parasympathetic branches of the autonomic nervous system (ANS).…”
Section: Measuring Active and Passive Fatigue With Cardiac Measuresmentioning
confidence: 99%
“…Scholars have used RMSSD, for example, to study sleepiness and drowsiness (for a recent review, see Matuz et al, 2020), self-regulation (e.g., Zahn et al, 2016), and stress recovery (e.g., Loerbroks et al, 2010) . Most of these studies have been conducted in laboratories (e.g., Burlacu et al, 2021; Kaida et al, 2007) and a few in real-road driving studies (Buendia et al, 2019; Jung et al, 2014; Persson et al, 2020). Repeated HRV monitoring in office-based field studies, however, is still scarce.…”
Section: Measuring Active and Passive Fatigue With Cardiac Measuresmentioning
confidence: 99%
“…For example, Kim et al (2018) described that an HRV analysis can function as a label for psychological stress when necessary [2]. HRV has been explored for monitoring car drivers' drowsiness, exhaustion, and anxiety levels [11]. Similarly, an HRV analysis has also found applications in detecting athletic performance and fatigue and assessing depression, anxiety, and other chronic conditions [12].…”
Section: Introductionmentioning
confidence: 99%